2016
DOI: 10.1111/ecc.12497
|View full text |Cite
|
Sign up to set email alerts
|

Men's help‐seeking in the first year after diagnosis of localised prostate cancer

Abstract: This study describes sources of support utilised by men with localised prostate cancer in the first year after diagnosis and examines characteristics associated with help‐seeking for men with unmet needs. A cross‐sectional survey of 331 patients from a population‐based sample who were in the first year after diagnosis (M = 9.6, SD = 1.9) was conducted to assess sources of support, unmet supportive care needs, domain‐specific quality of life and psychological distress. Overall, 82% of men reported unmet support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 49 publications
6
47
0
1
Order By: Relevance
“…partners, family & friends; Ettridge et al, ). Even men with localised prostate cancer are reluctant to seek help for their prostate‐related concerns within the year following diagnosis (40%) and few had accessed psychological support (Hyde et al, ). This sits within a context where men's general help‐seeking behaviour is known to be low for both health and psychological problems (Yousaf, Grunfeld, & Hunter, ).…”
Section: Discussionmentioning
confidence: 99%
“…partners, family & friends; Ettridge et al, ). Even men with localised prostate cancer are reluctant to seek help for their prostate‐related concerns within the year following diagnosis (40%) and few had accessed psychological support (Hyde et al, ). This sits within a context where men's general help‐seeking behaviour is known to be low for both health and psychological problems (Yousaf, Grunfeld, & Hunter, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of research investigating PCa patients' needs for support around body image issues. In general, previous studies found that PCa patients are often reluctant to seek psychological help . This reluctance might be related to stereotypical views of masculinity where seeking help is considered inappropriate .…”
Section: Introductionmentioning
confidence: 94%
“…Up to 75% of men treated for localised PCa report severe and persistent treatment side‐effects including sexual dysfunction, poor urinary or bowel function . Psychosocial concerns are prevalent with 30%‐50% of PCa survivors reporting unmet sexuality, psychological, and health system and information needs and 10%‐23% of men clinically distressed . Risk of suicide is increased after PCa diagnosis and can persist for a decade or more .…”
Section: Introductionmentioning
confidence: 99%